Service Quality Evaluation of Ancient City Scenic Spots Based on Tourists' Perceptions: An Example of Qingzhou Ancient - Yuliang, He; Qistina Donna, Lee Abdullah (2023)
From the perspective of tourist service perception, this study is the first to evaluate the service quality of the Qingzhou Ancient City tourist scenic area. The study adopts the SERVQUAL model and modifies it into a tourist service quality model specifically designed for ancient city scenic areas to measure the gap between tourists' perceived service quality and expected service quality in the context of the ancient city scenic area. The study also examines the influence of each dimension of this model on tourist satisfaction. Qingzhou Ancient City is chosen as a case study because it has a relatively high rating among ancient city scenic areas in China. The results indicate that tourists' overall satisfaction with the service in Qingzhou Ancient City is average. Among the six dimensions of this model, "historical and cultural significance," "assurance," and "empathy" are identified as key predictors of tourist satisfaction. This paper discusses the research findings and elucidates their managerial implications.